Opioids, chronic pain, and addiction in primary care. - Barry, Declan T; Irwin, Kevin S; Jones, Emlyn S; Becker, William C; Tetrault, Jeanette M; Sullivan, Lynn E; Hansen, Helena; O'Connor, Patrick G; Schottenfeld, Richard S; Fiellin, David A (The journal of pain : official journal of the American Pain Society, 2010)
Research has largely ignored the systematic examination of physicians' attitudes towards providing care for patients with chronic noncancer pain. The objective of this study was to identify barriers and facilitators to opioid treatment of chronic noncancer pain patients by office-based medical providers. We used a qualitative study design using individual and group interviews. Participants were 23 office-based physicians in New England. Interviews were audiotaped, transcribed, and systematically coded by a multidisciplinary team using the constant comparative method. Physician barriers included absence of objective or physiological measures of pain; lack of expertise in the treatment of chronic pain and coexisting disorders, including addiction; lack of interest in pain management; patients' aberrant behaviors; and physicians' attitudes toward prescribing opioid analgesics. Physician facilitators included promoting continuity of patient care and the use of opioid agreements. Physicians' perceptions of patient-related barriers included lack of physician responsiveness to patients' pain reports, negative attitudes toward opioid analgesics, concerns about cost, and patients' low motivation for pain treatment. Perceived logistical barriers included lack of appropriate pain management and addiction referral options, limited information regarding diagnostic workup, limited insurance coverage for pain management services, limited ancillary support for physicians, and insufficient time. Addressing these barriers to pain treatment will be crucial to improving pain management service delivery. PERSPECTIVE: This article demonstrates that perceived barriers to treating patients with chronic noncancer pain are common among office-based physicians. Addressing these barriers in physician training and in existing office-based programs might benefit both noncancer chronic pain patients and their medical providers.
Keywords: Analgesics, Opioid; Attitude to Health; Chronic Disease; Female; Humans; Male; Opioid-Related Disorders; Pain; Physician's Practice Patterns